2021
DOI: 10.3390/plants10081708
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract from Leaves of Citrus unshiu Attenuates Lipopolysaccharide-Induced Inflammatory Responses in a Mouse Model of Systemic Inflammation

Abstract: Inflammation is related to various life-threatening diseases including cancer, neurodegenerative diseases, and metabolic syndrome. Because macrophages are prominent inflammatory cells, regulation of macrophage activation is a key issue to control the onset of inflammation-associated diseases. In this study, we aimed to evaluate the potential anti-inflammatory activity of Citrus unshiu leaf extract (CLE) and to elucidate the mechanism underlying its anti-inflammatory effect. We found the inhibitory activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Based on previous research (Pandey et al, 2024) which mentions several components contained in clove and following the method by Nishi et al (2021), the water extraction of clove components was performed as followings. Clove powder was suspended in distilled water at 100 mg/mL and homogenized overnight at 12°C.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous research (Pandey et al, 2024) which mentions several components contained in clove and following the method by Nishi et al (2021), the water extraction of clove components was performed as followings. Clove powder was suspended in distilled water at 100 mg/mL and homogenized overnight at 12°C.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Inflammatory signaling pathways such as MAPK and NF-κB are important transcription factors in the inflammation-regulating system (Nishi et al, 2021). Therefore, to investigate the potential mechanism of the anti-inflammatory effect of CWE, the effect of CWE on the essential intracellular signaling pathways such as MAPK and NF-κB, and the protein expression level of iNOS, were investigated using Western blot analysis.…”
Section: Effect Of Cwe On Inos Expression and Mapk And Nf-κb Signalin...mentioning
confidence: 99%
“…In particular, the therapeutic effects of the peel covering C. unshiu have received more attention than other parts of the plant, because it exerts outstanding antioxidant effects compared to the pulp owing to its high mineral composition [ 13 , 14 ]. C. unshiu peel is widely used as a therapeutic agent for clinical purposes, such as neuropathic pain [ 15 ], cervical cancer [ 16 ], nonalcoholic fatty liver [ 17 ], hyperglycemia [ 18 ], pancreatic cancer [ 19 ], and systemic inflammation [ 20 ]. This raw material can also be processed using various extraction protocols, as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, water or ethanol extraction is a commonly used method to extract flavonoids from natural substances, hence, many studies employing solvent-extracted CUP have been conducted. For example, the ethanol derivative of CUP ameliorated oxidative stress by suppressing nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2 expression (NOX2) in a chemotherapy-induced neuropathic pain animal model [ 15 ] and decreasing the expression levels of pro-inflammatory cytokines, such as interleukin (IL)-6, interferon (IFN)-γ, and tumor necrosis factor-alpha (TNFα), in a type 2 diabetes and systemic inflammation mouse model [ 18 , 20 ]. Moreover, water extracts of CUP have been reported to attenuate dextran sulfate sodium-induced colitis by regulating the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in a recent study, Citrus unshiu peel was shown to have various pharmacological effects against viral infection, depression, obesity, and inflammation [ 11 14 ]. In the studies of Noh et al and Karthikeyan et al, it was reported that the Citrus unshiu peel exhibits anti-inflammatory effects in LPS stimulated RAW264.7 [ 15 , 16 ], and in the study of Nishi et al, the Citrus unshiu peel relieves inflammation through the NF- κ Bp65 and MAPK pathways in the model of systemic inflammation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%